A Civil Tongue Justice, Dialogue, and the Politics of Pluralism - Kingwell, Mark (Penn State University Press, 2021)
This book is about a widely shared desire: the desire among citizens for a vibrant and effective social discourse of legitimation. It therefore begins with the conviction that what political philosophy can provide citizens is not further theories of the good life but instead directions for talking about how to justify the choices they make-or, in brief, ";just talking.";As part of the general trend away from the aridity of Kantian universalism in political philosophy, thinkers as diverse as Bruce Ackerman, Jürgen Habermas, Alasdair MacIntyre, and Richard Rorty have taken a ";dialogic turn"; that seeks to understand the determination of principles of justice as a cooperative task, achieved in some kind of social dialogue among real citizens. In one way or another, however, each of these different variations on the dialogic model fail to provide fully satisfactory answers, Mark Kingwell shows. Drawing on their strengths, he presents another model he calls ";justice as civility,"; which makes original use of the popular literature on etiquette and work in sociolinguistics to develop a more adequate theory of dialogic justice
Description based on online resource; title from PDF title page (publisher's Web site, viewed 21. Jun 2021)
Keywords: PHILOSOPHY / Ethics & Moral Philosophy; Courtesy; Courtoisie; Cultural pluralism; Dialogue; Etiquette; Justice; Pluralisme; Savoir-vivre